Zostera marina seedling emergence count in field experiments, Kiel, Germany (2023) - A Zander; Tadhg O extquotesingleCorcora; Anna-Christina Bockelmann; Thorsten B H Reusch; Angela Stevenson (PANGAEA, 2025)
Seed-based seagrass restoration is expanding globally, to speed up the slow natural recolonization success of Zostera marina meadows. This study aimed to find practical guidelines to enhance seed-based restoration efforts in the German Baltic Sea, and other regions. To this end, parallel field and laboratory experiments were conducted, to examine the effects of six biotic and abiotic factors on seedling emergence (germination) over time. Seeds were collected by snorkelers from two sites (Falckenstein, Kiekut) in Schleswig-Holstein, Germany between July and August 2022. In the field, located in Kiel, Germany, 62 plots (50 x 50 cm) were sown with 100 seeds each of different seed coat colours (mixed from both sites) at three sowing time points (February, March, April 2023). Seedling and Arenicola marina mounds were counted biweekly from April until August 2023. Kiel Fjord temperature and salinity were taken from (Hiebenthal et. al., 2023).
In: Zander, A et al. (2025): Zostera marina seedling emergence count under varying salinity, temperature, seed colour, sowing time & Arenicola marina bioturbation in field & lab experiments, Kiel, Germany (2023) [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.984654